Behavioral and Neurodynamic Effects of Word Learning on Phonotactic Repair - Gow, David W.; Schoenhaut, Adriana; Avcu, Enes; Ahlfors, Seppo P. (Frontiers in Psychology, 2021)
Processes governing the creation, perception and production of spoken words are sensitive to the patterning of speech sounds in the words language users know. Generative linguistic theory suggests that listeners infer constraints on possible sound patterning from the lexicon and apply these constraints to all aspects of word use. In contrast, emergentist accounts suggest that these phonotactic constraints are a product of interactive associative mapping with items in the lexicon. To determine the degree to which phonotactic constraints are lexically mediated, we observed the effects of learning new words that violate English phonotactic constraints (e.g. srigin) on phonotactic perceptual repair processes in nonword CCV stimuli (e.g. /sre/). Subjects who learned such words were less likely to “repair” illegal onset clusters (/sr/) and report them as legal ones (/∫r/) . Effective connectivity analyses of MRI-constrained reconstructions of simultaneously collected MEG and EEG data showed that these behavioral shifts were accompanied by changes in the strength of influences of lexical areas on acoustic-phonetic areas. These results strengthen the interpretation of previous results suggesting that phonotactic constraints on perception are produced by top-down lexical influences on speech processing.